The Role of Islamic Education In Forming a Creative and Innovative Person: The Role of Islamic Education In Forming a Creative and Innovative Person - Siti Perawati; Silvy Damayanti P.; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
Islam is the religion brought by the Prophet Muhammad SAW. With the holy book of the Qur'an. Islam is the last religion that is acceptable and is derived from the revelations of Allah SWT. it was revealed to mankind through the angel Jibril to the Prophet Muhammad SAW. as a messenger of Allah who teaches about the Esaan of God, the salvation of the hereafter, the peace of the world, the rule of life and so on with the Qur'an as its scripture. Islamic religious education is a compulsory subject from basic education to higher education given to students who are Muslim. Islamic religious education is very strategic in shaping the personality of children in accordance with their personality to be a true Muslim. In order for Islamic religious education materials to be more easily understood by students, every teacher must be able to create creative and innovative learning methods.